The Legal Protection of Well-Known Service Trademark (The Case of Inter-Continental Vs The Intercontinental) - Nanda Riwanto1, Agung Sujatmiko1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The competition in the field of international services has increased the potential for copyright infringement of well-known service marks. Accordingly, it is necessary to examine the criteria for well-known service marks and legal protection to protect the trademarks’ copyright. This paper analyzes the criteria for well-known service marks according to the instruments of international law and national law. Besides, this study aims to investigate the forms of well-known service mark violations and the efforts to recover the trademarks. The method employed in this study was normative legal research. That method was used since this thesis examined the norms in the laws and regulations as well as the judgments relating to the trademarks to find the law against the issue addressed by utilizing statute approach and conceptual approach. In the case of INTER-CONTINENTAL v. the intercontinental, the trademark violation occurred was brand dilution. The parties in the INTER-CONTINENTAL v. Intercontinental case could resolve their dispute through alternative dispute resolution in the form of mediation, conciliation, or arbitration. In addition, the act of trademarks counterfeiting and piracy may be subjected to criminal sanctions according to the provisions of the applicable Trademark Law. The infringement of trademark copyrights is a detrimental act for the trademark’s legal owner. The settlement of trademark infringement can be conducted through criminal channels and alternative dispute resolution by mediation, conciliation, or arbitration